Examining concern about climate change and local environmental changes from an ecosystem service perspective in the Western U.S. Issue 101 (November 2019) - Cornell, Joseph D.; Quintas-Soriano, Cristina; Running, Katrina; Castro, Antonio J.
Highlights: This research combines the ecosystem service framework with climate change concerns analysis. Analysis of how ecosystem services priorities vary between people with different views about climate change Respondents who did not report climate change concern often recognized that climate change affect services. Designed to guide policymaking to communicate more effectively about climate-related effects. Abstract: Globally, concern about climate change and awareness of its impacts on local environments is not uniform between or within countries. In the U.S., variation in the public's perception of climate change may be due to differences in personal experience, knowledge, and priorities. The ecosystem services framework provides an opportunity for understanding this variation by connecting what people value about their local ecosystems with their understanding of how changes in climate may impact specific services. We use a social survey administered in the western U.S. to analyze how people prioritize different ecosystem services and how these priorities vary between people with different views about climate change. Overall, 70% of our sample reported concern about climate change, but there were interesting differences in which ecosystem services concerned and unconcerned respondents valued most. Also, many of those respondents who did not report climate change concern often recognized that climate change will affect services they valued most. These results highlight that local publics can be either uninterested in or unworried by scientific findings about the human causes of climate change, but still realize that the environment is changing and that these changes will impact the ecosystem services upon which they depend. Combining the ecosystem service framework with questions about local environmental change provides details on the environmental values of people with different opinions about climate change, and we argue a more comprehensive understanding of this dynamic should help guide scientists and policymakers communicate more effectively about climate-related effects and potential responses.